Characterization of Submarine Groundwater Discharge in Mabini, Batangas: Linking Geology, Submarine Groundwater Discharge and Coastal Ecosystems - Rodolfo, Raymond (Archīum Ateneo, 2019)
Mabini, Batangas is home to popular dive sites frequented by local and foreign divers. It lies within the Verde Island Passage Marine Corridor (VIPMC) which is hailed as the "Center of the Center of Marine Biodiversity" according to a research done by Kent Carpenter and Victor Springer in 2005. Aside from being located in an area of high marine biodiversity, Mabini is also situated in a volcanic area with distinct geologic structures. It is situated at the southern tip of the Calumpan Peninsula which lies within the Macolod Corridor defined by gravity faults and volcanic ridges as a result of active subduction along the southern segment of the Manila Trench. Submarine groundwater discharge (SGD) is an important component of the hydrologic cycle connecting the terrestrial and marine environments serving as a pathway for nutrients as well as contaminants from the ridge towards the reef ecosystem. SGD needs to be characterized in order to understand the availability and quality of groundwater and its effect on coastal processes linking various disciplines such as geology, hydrology, biology and ecology. In the case of SGD in the coastal waters of Mabini, there seems to be a strong link between the geology and the coastal ecosystems in the area as exhibited in the presence of hot underwater springs and biodiversity in the adjoining dive sites. The SGD at the study area, which can be detected through high radon concentrations in the coastal waters, is controlled by geologic structures such as faults and hydrothermal features.